Режими диспозитивності у правовому регулюванні договірних відносин - Чалий, Ю. І.; Chalyi, Yu. I.; Юрій Чалий (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 2. - С. 72-83, 2023)
Наголошено на необхідність подальшої диференціації режимів диспозитивності в регулюванні договірних відносин. Найвищий ступінь диспозитивності має проявлятися у правовому регулюванні договірних відносин за участі підприємців, найнижчий – у договірних зв’язках, де сторонами є підприємці та споживачі. Серединне положення за інтенсивністю прояву диспозитивних положень законодавства має посідати режим упорядкування договірних відносин, що виникають між фізичними особами-непідприємцями, а також між фізичними особами-непідприємцями та юридичними особами-непідприємцями.

It has been concluded that there is a need for further differentiation of the dispositivity regimes in the regulation of contractual relations. The contractual relationship "entrepreneur - entrepreneur" requires the highest possible degree of discretionary provisions of the legislation governing these relations, but the freedom of contract in such relations may be limited based on the need to maintain public order, public morality, restrain monopoly, protect third parties from negative externalities arising from certain types of economic activity. In the legal regulation of contractual relations between entrepreneurs and consumers, discretion should be applied to a relatively minimal extent. In this regard, the legislator imperatively determines the terms of contracts on which the parties must reach an agreement; regulates sample (exemplary, typical) contracts; imposes pre-contractual obligations on entrepreneurs to fully inform consumers about the properties of products offered for sale; establishes general prohibitions on unfair contractual terms; provides consumers with certain guarantees regarding the conclusion, amendment and termination of contracts, etc. The regime of regulation of contractual relations involving individuals who are non-entrepreneurs occupies a middle position between the two above legal regimes and provides for: establishment of a relatively smaller number of legal forms of contracts that may be concluded by citizens; determination of conditions mandatory for the conclusion of contracts in the legislation; consolidation of a general prohibition on unfair contractual terms; establishment of a wider list of contracts subject to notarisation; introduction of judicial control over compliance by the parties with the requirements of the law regarding the validity of contracts, etc. Such a differentiated approach allows establishing the most equitable regime for regulating contractual relations. The boundaries of these legal regimes are difficult to fix in legislation in a certain stable state, and must be constantly adjusted by law enforcement practice.

Отмечена необходимость дальнейшей дифференциации режимов диспозитивности в регулировании договорных отношений. Самая высокая степень диспозитивности должна проявляться в правовом регулировании договорных отношений с участием предпринимателей, самая низкая – в договорных связях, где сторонами являются предприниматели и потребители. Срединное положение по интенсивности проявления диспозитивных положений законодательства должно занимать режим составления договорных отношений, возникающих между физическими лицами-непредпринимателями, как и между физическими лицами-непредпринимателями и юридическими лицами-непредпринимателями.
Regimes of dispositivity in the legal regulation of contractual relations
Keywords: цивільно-правовий договір; режими диспозитивності впорядкування договірних відносин; диспозитивні норми; імперативні норми; свобода договору; обмеження свободи договору; civil law contract; regimes of dispositivity of contractual relations; dispositive rules; imperative rules; freedom of contract; restriction of freedom of contract; гражданско-правовой договор; режимы диспозитивности упорядочения договорных отношений; диспозитивные нормы; императивные нормы; свобода договора; ограничение свободы договора